Orange is the new black. Season six [videorecording (DVD)] - Trim, Michael (Television director); Burley, Mark A; Schilling, Taylor, 1984-; Lyonne, Natasha; Aduba, Uzo; Kerman, Piper (Lionsgate, 2019)
A woman is incarcerated for fifteen months in a federal prison after being convicted of drug trafficking and must learn to adapt to her new prison life.